Prevalence of Visual Impairment in Preschool Children in Southern China - Wang, Hongxi; Qiu, Kunliang; Yin, Shengjie; Du, Yali; Chen, Binyao; Jiang, Jiao; Deng, Dandan; Zhang, Mingzhi (Frontiers in Public Health, 2022)
Purpose The goal of this study is to assess the prevalence and distribution of visual impairment in preschool children in southern China. Methods Preschool children aged 36–83 months were enrolled in a vision screening program in Shantou City. Visual acuity test and non-cycloplegic refraction were conducted. According to the American Academy of Ophthalmology (AAO) guidelines, visual impairment was defined as uncorrected visual acuity (UCVA) in either eye <20/50, 20/40, and 20/32 in children aged 36–47, 48–59, and 60–83 months, respectively, as well as an interocular difference (IOD) of ≥ two lines of UCVA. Results The UCVA test was successfully performed on 7,880 children (94.6% of the enrolled population). A total of 938 (11.9%; 95% CI 11.2–12.6) children were found to have reduced UCVA in the worse eye, and 393 (5%; 95% CI 4.5–5.5) of the children had an IOD of two or more lines. Combining the reduced UCVA with the IOD criteria identified 1,032 (13.1%; 95% CI 12.4–13.8) children with visual impairment. UCVA in preschool children improves with age naturally and boys have slightly better age-adjusted UCVA than girls. Causes of reduced visual acuity included uncorrected refractive error, amblyopia, congenital cataract, and others. The cylindrical diopter in the right eye of children with reduced vison was higher than that of children with normal vision (1.19 ± 1.05 vs. 0.52 ± 0.49, P < 0.001). A total of 146 (1.9%, 95% CI 1.6–2.2) of the preschool children wore spectacles. The proportion of wearing spectacles increased with age (χ2 = 35.714, P < 0.001), but with IOD increasing by.1 logMAR, the odds of wearing spectacles decreased by 44.8%. Conclusion This study provided data on the prevalence of visual impairment in preschool children in China by large-scale school-based vision screening. Further studies should be conducted to verify the benefit from vision screening.